TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA DI SIDOARJO (STUDI KASUS PUTUSAN PN SIDOARJO NOMOR 230/PID.B/2023/PN SDA) - Mohammad Fikri Alfada Wijaya; Syahrul Borman; Vieta Imelda Cornelis (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
This research discusses the elements of criminal acts and the considerations of the panel of judges in one of the cases which was a crime of murder. The author is interested in studying more deeply the application of law and the legal considerations of the panel of judges regarding the crime of murder in the case study of the Sidoarjo District Court decision Number 230/Pid.B/2023/PN Sda dated 21 June 2023, especially as there is an interesting thing about the perpetrator before committing murder with the intention of carrying a sharp sickle type weapon which can be subject to Article 340 of the Criminal Code because it meets the elements of